Ekspresi Takut Sebagai Ide Penciptaan Karya Seni Lukis - Giva Kurnia; Miswar Miswar; Yunis Muler (V-art: Journal of Fine Art, 2022)
The artist's experience in childhood with bullying and discrimination is the source of the expression of fear depicted in this work. This experience creates fear that makes artists worse off, reluctant to socialize, and withdrawn. This fear is used as an idea in the creation of paintings. The scope of experience is focused on poor social interactions at school. The form of work created uses a representational approach with changes in the form of distortion and transformation in a surreal style. The method of creation used is preparation, namely reflecting on and recalling the disturbing past. The next stage is the design stage, namely, making alternative sketches. The forming stage begins with the process of transferring the sketch to the canvas and ends with the painting process. After completing all these stages, the work is exhibited. The painting was made using the aquarel technique and the plaque technique. The materials used are acrylic paint and canvas. The creation of this work has resulted in five paintings entitled "Complaint," "Confused," "Response," "Self Opera," and "The Past."